Molecular ecology progress of anaerobic ammonia oxidation reaction - ZHU Chen; ZHANG Naifang; XU Chenchao; ZHANG Kaihang; CHENG Lei (浙江大学学报. 农业与生命科学版, 2019)
The anaerobic ammonia oxidation (ANAMMOX) reaction with nitrite as an electron acceptor and nitrogen as a product is mediated by bacteria which belong to Planctomycetales. The ANAMMOX bacteria are ubiquitous and play an essential role in global nitrogen cycle. Here, combining the introduction of methods and techniques frequently used, we summarized the progress of ANAMMOX and divided the research history into three levels: 1) community; 2) cell; 3) molecular and omics analysis. Based on their introduction, we clarified the progress in ANAMMOX driven by them, and discussed some questions exiting in this field and put forward new methods and techniques that may be helpful.